Stiffness quantification of conductive polymers for bioelectrodes. Issue 9 (26th February 2014) - Hassarati, Rachelle T.; Goding, Josef A.; Baek, Sungchul; Patton, Alexander J.; Poole‐Warren, Laura A.; Green, Rylie A.
ABSTRACT Conductive polymer (CP) coatings can improve the performance of metallic bioelectrodes in implantable devices, a benefit which is partially attributed to the "softer" material interface. However, due to the nature of CP fabrication on metallic substrates, accurate quantification of mechanical properties has been difficult to achieve. This study demonstrates that peak‐force quantitative nanomechanical mapping (PF‐QNM) is a robust technique for determining the modulus of CP coatings. The effect of dopant size, chemistry, and film hydration on the mechanical properties of poly(3, 4‐ethylene dioxythiophene) (PEDOT) is also examined. Analysis of PEDOT doped with poly(styrene sulfonate) produced across five different thicknesses confirms the utility of PF‐QNM in yielding quantitative, repeatable moduli in both the dry and hydrated state. By doping PEDOT with paratoluene sulfonate and perchlorate (ClO4) it is shown that the hydrophilicity and the size of the dopant are both critical factors influencing CP mechanical properties in the hydrated environment. © 2014 Wiley Periodicals, Inc. J. Polym. Sci., Part B: Polym. Phys. 2014, 52, 666–675